2003
DOI: 10.1007/s103100300017
|View full text |Cite
|
Sign up to set email alerts
|

Positioning precision and sampling number of DGPS under forest canopies

Abstract: Experimental results were studied to determine the relationships between positioning precision of a differential global positioning system (DGPS) and forest type, antenna height, and season, and to clarify the relationship between sampling number and the convergence of positioning precision. Observation was carried out for 24 h. Mean circular area probability (CEP 95 ) was 2.80 m for deciduous broadleaved trees, and 4.99 m for conifers. The mean CEP 95 taken at 7 m height (3.14 m) was higher than that at 1 m h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Research regarding end-user practical recommendations has focused on determining GPS receiver performance under different forest conditions by comparing receivers ͑Karsky et al 2000; positioning methods ͑Naes-set et al 2000;Naesset and Jonmeister 2002;Hasegawa and Yoshimura 2003;Sawaguchi et al 2003͒. Techniques such as differential global positioning system ͑DGPS͒ improve precision and accuracy under tree canopies ͑Hasegawa and Yoshimura 2003; Sawaguchi et al 2003;Satirapod et al 2003; Tiberius and Kenselaar 2003͒ but they are not available for recreational GPS receivers, which are cheaper, easier to use, and require less user training than topographic GPS receivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research regarding end-user practical recommendations has focused on determining GPS receiver performance under different forest conditions by comparing receivers ͑Karsky et al 2000; positioning methods ͑Naes-set et al 2000;Naesset and Jonmeister 2002;Hasegawa and Yoshimura 2003;Sawaguchi et al 2003͒. Techniques such as differential global positioning system ͑DGPS͒ improve precision and accuracy under tree canopies ͑Hasegawa and Yoshimura 2003; Sawaguchi et al 2003;Satirapod et al 2003; Tiberius and Kenselaar 2003͒ but they are not available for recreational GPS receivers, which are cheaper, easier to use, and require less user training than topographic GPS receivers.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques such as differential global positioning system ͑DGPS͒ improve precision and accuracy under tree canopies ͑Hasegawa and Yoshimura 2003; Sawaguchi et al 2003;Satirapod et al 2003; Tiberius and Kenselaar 2003͒ but they are not available for recreational GPS receivers, which are cheaper, easier to use, and require less user training than topographic GPS receivers. Therefore, the main issue regarding recreational GPS receivers has been determining their performance under different forest conditions, and whether the precision and accuracy achieved satisfy mapping and engineering requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Martin et al [2000] attributed errors under the canopy to PDOP, while Jiang et al [2008] asserted that a better performance is obtained with longer periods of observation that result in lower PDOP values. Proposed solutions for improving reception range from raising the antenna height [Gandasecaet al, 2001;Sawaguchi et al, 2003;, using translocation instead of point-positioning [Tsuyuki, 1994], and increasing the survey period [Yoshimura and Hasegawa, 2006]. Hasegawa and Yoshimura [2003] developed regression models based on the observation period and canopy opening, using the canopy photographs mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Hasegawa and Yoshimura [8] achieved a mean error of a 1 to 30-min observation varied between 0.029-0.226 m (without closed tree canopies) and it was 0.415-0.894 m (with closed tree canopies), using Dual-frequency GPS receivers by carrier phase DGPS static surveying. Sawaguchi and others [3] using DGPS got mean CEP95 = 2.80 m for deciduous broadleaved trees and 4.99 m for conifers. Additionally they demonstrated that positioning precision was not noticeably improved if the sampling number was around 10.…”
Section: Measuring the Accuracy And Precision Of The Garmin Gps Positmentioning
confidence: 99%
“…The most common measures used in previous works to estimate GPS accuracy and precision are CEP (circular error probable), RMS (root mean square error) and DRMS (distance root mean square error). Sawaguchi and others [3] define CEP as the value which half of the data points fall within a circle of this radius centered on truth and a half lie outside this circle and use CEP to estimate GPS positioning at different forest type, antenna height, and season, and to clarify the relationship between sampling number and the convergence of positioning precision. RMS value indicates that approximately 68 percent of the data points fall within this true distance.…”
Section: Measuring the Accuracy And Precision Of The Garmin Gps Positmentioning
confidence: 99%